Pernikahan Mualaf Belum Sirkumsisi (Khitan) Dalam Islam - Burhan, Ali; Arifin, Samsul (Al-Adillah: Jurnal Hukum Islam, 2024)
Abstract This journal discusses the issue of the validity of marriage for a convert to Islam who has not yet circumcised (circumcision). The results of the research can be presented or explained in this journal that marriage for someone, especially for converts who have not been circumcised (Circumcision) is still considered valid as long as the conditions and harmony in marriage are fulfilled. Because the ulama do not require circumcision (Circumcision) as a condition for marriage. Likewise, in the law of circumcision (Circumcision) there are differences of opinion among the priests of the sect. Jurnal ini membahas tentang permasalahan keabsahan pernikahan bagi seorang mualaf yang belum sirkumsisi ( khitan ). Adapun hasil penelitian dapat dipaparkan atau dijelaskan dalam jurnal ini bahwa pernikahan bagi seseorang khususnya bagi mualaf yang belum sirkumsisi ( Khitan ) tetap dihukumi sah selama syarat dan rukun dalam pernikahan terpenuhi. Karena para ulama tidak mensyaratkan kepada sirkumsisi ( Khitan ) sebagai sebuah syarat dalam pernikahan. begitu pula di dalam hukum sirkumsisi ( Khitan ) terdapat perbedaan pendapat di kalangan para imam mazhab.